Coevolution of Siglec-11 and Siglec-16 via gene conversion in primates. Issue 1 (December 2017) - Hayakawa, Toshiyuki; Khedri, Zahra; Schwarz, Flavio; Landig, Corinna; Liang, Suh-Yuen; Yu, Hai; Chen, Xi; Fujito, Naoko; Satta, Yoko; Varki, Ajit; Angata, Takashi
Abstract Background Siglecs-11 and -16 are members of the sialic acid recognizing Ig-like lectin family, and expressed in same cells. Siglec-11 functions as an inhibitory receptor, whereas Siglec-16 exhibits activating properties. In humans, SIGLEC11 andSIGLEC16 gene sequences are extremely similar in the region encoding the extracellular domain due to gene conversions. HumanSIGLEC11 was converted by the nonfunctionalSIGLEC16P allele, and the convertedSIGLEC11 allele became fixed in humans, possibly because it provides novel neuroprotective functions in brain microglia. However, the detailed evolutionary history ofSIGLEC11 andSIGLEC16 in other primates remains unclear. Results We analyzedSIGLEC11 andSIGLEC16 gene sequences of multiple primate species, and examined glycan binding profiles of these Siglecs. The phylogenetic tree demonstrated that gene conversions betweenSIGLEC11 andSIGLEC16 occurred in the region including the exon encoding the sialic acid binding domain in every primate examined. Functional assays showed that glycan binding preference is similar between Siglec-11 and Siglec-16 in all analyzed hominid species. Taken together with the fact that Siglec-11 and Siglec-16 are expressed in the same cells, Siglec-11 and Siglec-16 are regarded as paired receptors that have maintained similar ligand binding preferences via gene conversions. Relaxed functional constraints were detected on theSIGLEC11 andSIGLEC16 exons that underwent gene conversions, possibly contributing to the evolutionary acceptance of repeated gene conversions. The frequency of nonfunctionalSIGLEC16P alleles is much higher than that ofSIGLEC16 alleles in every human population. Conclusions Our findings indicate that Siglec-11 and Siglec-16 have been maintained as paired receptors by repeated gene conversions under relaxed functional constraints in the primate lineage. The high prevalence of the nonfunctionalSIGLEC16P allele and the fixation of the convertedSIGLEC11 imply that the loss of Siglec-16 and the gain of Siglec-11 in microglia might have been favored during the evolution of human lineage.